Rilmenidine Protects Against Joint Damage in MIA-induced Model of Osteoarthritis in Rats - Osman Kukula; Mustafa Nusret Çiçekli; Caner Günaydın; Seda Kırmızıkan; Selenay Sevinç Şarklıoğlu (Borneo Journal of Pharmacy, 2024)
Osteoarthritis is a common problem, and its incidence significantly increases with age. Patients suffer from excruciating pain while moving, and currently, major treatment options consist of surgery. Rilmenidine is a potent antihypertensive agent with a high affinity for imidazoline and alpha2 adrenergic receptors. Based on the knowledge that these receptors are also related to bone turnover and pain, we aimed to reveal the effect of rilmenidine on the osteoarthritis model in rats. Monosodium iodoacetate was used to induce osteoarthritis. Animals were treated with rilmenidine (0.5, 2 mg/kg) for 14 days. A hot plate test was performed to assess pain response before and end of the drug treatments, in addition to the walking track analysis. Twenty-four hours after the last drug treatment, serum levels of receptor activator of nuclear factor kappa-Β ligand and osteoprotegerin were measured. Hematoxylin eosin and safranin-O staining were used to evaluate monosodium iodoacetate and rilmenidine-induced changes in the hindlimb joints. Our results demonstrate that rilmenidine(2 mg/kg) prevented monosodium iodoacetate-induced thermal hyperalgesia with improved walking behavior in the walking track test. Additionally, rilmenidine(2 mg/kg) prevents monosodium iodoacetate-induced increase in the nuclear factor kappa-Β ligand and osteoprotegerin levels in the serum. Histopathological analysis shows that rilmenidine is protective on the joint capsules and matrix. Our results suggest that rilmenidine shows an antinociceptive effect on monosodium iodoacetate-induced osteoarthritis via improving bone turnover.